#1 First we simplify the expression,
(3 x 6) - ([4^2/2)
So first we do what's within the parenthesis because of PEMDA's
So 3 x 6 is 18
4 to the second power is 16
Now we divide 16 by 2 to get 18
So now we can subtract 8 from 18 to get 10.
So the answer is 10
#2 3 to the second power is 9
8 to the second power is 64
Now we can do 9 x 5 to get 45
45 divided by 9 is 5
Now 5 plus 64 is 69
#3
Divide: 75 / 5 = 15
Multiple: 15 * 2 = 30
Power: 2 ^ 3 = 8
Add: 30 + 8 = 38
Subtract: 11 - 8 = 3
Power: 3 ^ 2 = 9
Multiple: 4 * 9 = 36
Subtract: 38 - 36 = 2
So for number 3 it's 2
I hope this helped :)